Effect of backscattering on irradiation of electrical wire and cables by electron beam. (April 2022) - Jung, Seung-Tae; Pyo, Seong-Hwan; Kang, Won-Gu; Kim, Yu-Ri; Kim, Jin-Kyu; Nho, Young-Chang; Park, Jong-Seok; Choi, Jae-Hak; Kang, Chang M.
Abstract: An electron accelerator is an useful radiation source of crosslinking the polymers that are used for the insulation of wire and cable. By irradiation of polymer materials, chemical bonds are formed between polymer molecules, causing a three-dimensional insoluble network. Crosslinking of wire and cables are processed by electron beam while passing back and forth through the beam by using a wire handling system that consists of two solid drums displaced under the scanning beam. Multiple passes can prevent the overheating of the insulated wire or cables by allowing some of the heat from electron beam (EB) irradiation to dissipate between passes. The EB energy can penetrate the thickness of the insulation, and pass through wire or cables. Some of the beam will strike oxygen in air, leading to producing ozone. Usually a beam stopper is installed to reduce the formation of ozone. Striking of an accelerated electron beam to a target material produces elastic and inelastic collisions between electrons and atoms. Backscattered electrons are produced when the electron beam interacts more deeply with the target material. The incoming electrons experience elastic scattering as a result of direct collisions with the electron shell of an atom. Elastic scattering changes the trajectory of the incoming beam electrons when they interact with a target without significant change in their kinetic energy. In this study, MCNP6.2 program was used to study the effect of backscattered electrons from the target material on the energy deposition of cylinder model and cable sample during EB irradiation. Highlights: The backscattering effect was analyzed using MCNP program. A copper cylinder wound with CTA film was used as a model sample. Lead, copper, stainless steel, aluminum, and wood were selected as backscatters. The backscattering effect depends on the density of the backscattering material. Installing a beam stopper improved the absorbed dose on the lower part of the cable.